Transfemoral versus transapical transcatheter aortic valve implantation: a single-centre experience. (9th November 2018) - Reents, Wilko; Barth, Sebastian; Griese, Daniel P; Winkler, Sebastian; Babin-Ebell, Jörg; Kerber, Sebastian; Diegeler, Anno; Zacher, Michael; Hamm, Karsten
Abstract: OBJECTIVES: Transapical transcatheter aortic valve implantation (TAVI) is associated with increased mortality as compared to the transfemoral (TF) access. Possible mechanisms include different patient risk profiles as well as an intrinsic injury caused by the access route itself. METHODS: All consecutive patients scheduled for TAVI between January 2009 and June 2016 at a single centre were evaluated. A comparison of 30-day mortality and morbidity rates for patients undergoing TF or transapical (TA) TAVI was performed according to the criteria of the Valve Academic Research Consortium 2. RESULTS: During the investigated period, 1130 patients (TF: n  = 619, TA: n  = 511) were scheduled for TAVI. TA patients had a higher operative risk profile (logistic EuroSCORE: 24% vs 17%; P  < 0.001). Unadjusted 30-day mortality rate was higher in TA than in TF patients, albeit this difference was not significant [TA: 6.7%, TF: 4.8%; odds ratio (OR) 1.3 (0.8–2.3); P  = 0.216]. The multivariate logistic regression analysis revealed the logistic EuroSCORE and institutional experience, but not the access mode as independent predictors of 30-day mortality. Major access-site complications occurred with a similar frequency in both groups [TA: 9.4%; TF: 9.2%; OR 1.02 (0.68–1.53); P  = 0.915]. Unadjusted long-term mortality rate was higher after TA TAVI. After adjustment, the Cox regression analysis revealed similar long-term mortality rates after TF and TA TAVI [hazard ratio 1.1 (0.88–1.36)]. CONCLUSIONS: The increased mortality of patients undergoing TA TAVI is associated with the patient risk profile and the institutional experience but not with the access mode itself.